PENGARUH PERSEPSI NILAI TERHADAP MINAT BERKUNJUNG KEMBALI WISATAWAN PANTAI CAMPLONG DENGAN KEPUASAN SEBAGAI PEMEDIASI - Septiyanti, Fauziyah Mubaarokah; Jannah, Miftahul (Creative Research Management Journal, 2022)
This research was conducted with the aim of finding the effect of perceived value on revisit intention to return to Camplong beach by including tourist satisfaction as a mediating variable. The sample used is primary data obtained by distributing questionnaires to Camplong beach tourists with a total of 120 respondents. Samples were taken by using nonprobability sampling technique and the type of respondent was taken using purposive sampling technique. This research is a quantitative descriptive research using test instruments, regression analysis and mediation tests as tools to determine the effect of each variable. The results of the study show that price values and emotional values have a positive and significant effect on satisfaction. Social value does not show an effect on satisfaction. Satisfaction influences the intention to return positively and significantly. Satisfaction mediates the price value and emotional value on the revisit intention. However, it failed to mediate social value on the intention to return.